2011
DOI: 10.3233/dma-2011-0824
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of FOXE1 polyalanine tract in thyroid diseases: New insight on the role of FOXE1 in thyroid carcinoma

Abstract: FOXE1 polyalanine tract (poly-Ala) has been associated with thyroid dysgenesis. Recently, the SNP (rs1867277:-238G>A) within the FOXE1 5'UTR was involved in the genetic susceptibility to thyroid cancer (TC). In the aim to assess the influence of FOXE1 poly-Ala length on the genetic susceptibility to TC and autoimmune thyroid diseases (AITD), a case-control design (including 261 Tunisian AITD, 170 Spanish TC and respectively 171 and 218 matched healthy subjects) was performed. The effect of Ala length and rs186… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
1
29
1
2
Order By: Relevance
“…These SNPs demonstrated a significant association with Chernobyl radiation-related PTC in Belarusian patients (10). Furthermore, another SNP located in the FOXE1 promoter (rs1867277) and in the same LD region as rs965513 was associated with DTC in Spanish/Italian, Belarusian, and British cohorts (8,21,22). In this context, the risk allele ''A'' of the SNP rs1867277 is capable of augmenting FOXE1 transcription by creating a binding site for leucine zipper upstream stimulatory factors 1 and 2 (USF1/ USF2) (22).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These SNPs demonstrated a significant association with Chernobyl radiation-related PTC in Belarusian patients (10). Furthermore, another SNP located in the FOXE1 promoter (rs1867277) and in the same LD region as rs965513 was associated with DTC in Spanish/Italian, Belarusian, and British cohorts (8,21,22). In this context, the risk allele ''A'' of the SNP rs1867277 is capable of augmenting FOXE1 transcription by creating a binding site for leucine zipper upstream stimulatory factors 1 and 2 (USF1/ USF2) (22).…”
Section: Discussionmentioning
confidence: 92%
“…In this context, the risk allele ''A'' of the SNP rs1867277 is capable of augmenting FOXE1 transcription by creating a binding site for leucine zipper upstream stimulatory factors 1 and 2 (USF1/ USF2) (22). Also, in three recent studies, both the rs1867277 and the FOXE1 polyAla tract variants were associated with DTC cancer in Spanish, Australian, and Portuguese cohorts (20,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…FOXE1, which is also called TTF2 (Thyroid transcription factor 2), is a transcription factor involved in thyroid gland development (thyroid formation, migration and morphogenesis control [2023]) and in the maintenance of differentiation in the thyroid [24] and which is highly expressed in thyroid follicular cells [25, 56]. According to Goldgar DE and Eng C, multiple low- to moderate-penetrance genes (LPGs) interacting with each other and with the environment may result in thyroid cancer [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that the A allele of this SNP increases the transcriptional activity of the FOXE1 gene promoter, by the recruitment of leucine zipper upstream stimulatory factors 1 and 2 (Landa et al, 2009). Regarding the FOXE1 polyAla tract, it has been reported that it has 11-22 alanine residues, although FOXE1 14Ala and FOXE1 16Ala account for greater than 98% of reported alleles (Kallel et al, 2010). Some studies have suggested a functional consequence for the presence of polyAla expansions (>14) but not for contractions (414).…”
Section: Snpmentioning
confidence: 96%